Wage Claims, Incomes Policy, and the Path of Output and Inflation in a Formerly Centrally Planned Economy - Milesi-Ferretti, Gian. (Washington, D.C. : International Monetary Fund, 1992)
The corporate governance problem of state enterprises in former socialist economies can give rise to excessive wage claims and/or capital decumulation. This paper focuses on these problems, highlighting the dynamic links between wage behavior, the fiscal deficit, inflation and the capital stock. Wage controls have been widely advocated as a response to the corporate governance problem. We show that in the presence of excessive wage claims a system of wage controls can help to limit capital decumulation and reduce inflation, since wage moderation implies higher government revenues from the profit tax and therefore lower money creation. More specifically, it is shown that when wage levels are initially excessive a reduction in the degree of wage indexation is effective in lowering inflation if nominal wages do not provide, on average, full protection against future inflation.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet